2017
DOI: 10.1186/s40349-017-0084-0
|View full text |Cite
|
Sign up to set email alerts
|

Objective image analysis of real-time three-dimensional intraoperative ultrasound for intrinsic brain tumour surgery

Abstract: BackgroundThere is growing evidence that maximal surgical resection of primary intrinsic brain tumours is beneficial, both by improving progression free and overall survival and also by facilitating postoperative chemotherapy and radiotherapy. Hence, there has been an increase in the popularity of real-time intraoperative imaging in brain tumour surgery. The complex theatre arrangements, prohibitive cost and prolonged theatre time of intraoperative MRI have restricted its application. By comparison, intraopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Three-dimensional ultrasound (3DUS) is based on two-dimensional ultrasound (2DUS) imaging with the addition of the coronal section. Intraoperative 3DUS is a portable imaging technique that provides real-time imaging, which can be integrated into existing theater infrastructure without the need for its own dedicated suite [7]. Recently, 3DUS imaging has already been used for cardiac, obstetric, and gynecological applications [42].…”
Section: New Developments In Intraoperative Ultrasoundmentioning
confidence: 99%
See 3 more Smart Citations
“…Three-dimensional ultrasound (3DUS) is based on two-dimensional ultrasound (2DUS) imaging with the addition of the coronal section. Intraoperative 3DUS is a portable imaging technique that provides real-time imaging, which can be integrated into existing theater infrastructure without the need for its own dedicated suite [7]. Recently, 3DUS imaging has already been used for cardiac, obstetric, and gynecological applications [42].…”
Section: New Developments In Intraoperative Ultrasoundmentioning
confidence: 99%
“…Given that reconstructed images are clear and intuitive, they can be used to measure the size and volume of gliomas, as well as clearly display the 3D shape and spatial location of the lesion. This technique could provide accurate visualization of blood vessels, the ventricular system, lesions, and immediate complications, such as hematomas [7]. 3DUS can not only make up for the spatial imaging deficiency of two-dimensional ultrasound but also reduce artifacts produced after tumor resection [44].…”
Section: New Developments In Intraoperative Ultrasoundmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed the benefits of intraoperative ultrasound for achieving maximal safe resection in brain tumor surgery [10].…”
Section: Discussionmentioning
confidence: 99%